Adverse remodeling of the subpulmonary left ventricle in patient with systemic right ventricle is associated with clinical outcome. (13th July 2021) - Santens, B; Helsen, F; Van De Bruaene, A; De Meester, P; Budts, A; Troost, E; Moons, P; Claus, P; Rega, F; Bogaert, J; Budts, W
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): This research received project funding by KU Leuven Background  – Early recognition of adverse remodeling is important since outcome is unfavorable once patients with a systemic right ventricle (sRV) become symptomatic. We aimed assessing prognostic markers linked to short-term clinical evolution in this population.  Purpose  - We aimed assessing short-term clinical evolution and early prognostic markers of cardiac complications in adults with sRV (atrial switch repair for D-transposition of the great arteries (D-TGA) and congenitally corrected transposition of the great arteries (ccTGA)) based on detailed phenotyping.  Methods– Thirty-three patients with sRV underwent detailed phenotyping including exercise CMR. Adverse outcome was a composite of heart failure episode and tachyarrhythmia. Descriptive statistics and univariate cox regression analyses were performed.  Results  - Thirty-three patients (76% male) with sRV were followed over mean follow-up time of 3 years. Mean age was 40 ± 8 (range 26-57) years at latest follow-up. When compared to baseline, (I) most patients remained in NYHA functional class I (76%),   (II) the degree of severity of the SAVV regurgitation rose and (III) more electrical instability was documented at latest follow-up. Six (18%) of a total of nine events were counted as first cardiovascular events (9% heart failure, 9% arrhythmia). NTproBNP (HR 11.02 (95%CI 1.296-93.662), p= 0.028), oxygen pulse (HR 1.202 (95% CI 1.012-1.428), p = 0.037), left ventricle end diastolic volume index (LVEDVi) in rest (HR 1.046 (95% CI 1.002-1.092), p = 0.041) and during exercise (HR 1.035 (95% CI 1.002-1.069), p = 0.038),  stroke volume index (SVi) of the subpulmonary left ventricle (LV) in rest (HR 1.154 (95% CI 1.005-1.322), p = 0.038) and at peak exercise (HR 1.065 (95% CI 1.007-1.125), p = 0.026) were significantly associated with the first cardiovascular event (Figure 1A and B).  Conclusion – NTproBNP was by far the best prognostic marker for clinical outcome. Adverse remodelling with increase of LVEDVi and SVi of the subpulmonary LV at rest and during exercise were associated with worse clinical outcome. We theorize that remodeling of the subpulmonary ventricle might be an early sign of a failing sRV circulation (Figure 2).